The First Principles Study of Electronic and Optical Properties of TiO2 Isomers - Wu, Shufang; Liu, Tianmo; Qin, Wenyong; Chen, Cheng; Lei, Xiaofei; Zeng, Wen (Asian Journal of Chemistry, 2012)
The electronic and optical properties of three TiO2 isomers are systematically investigated by the first-principles calculations, using generalized gradient approximation based on the densityfunctional theory. Such electronic and optical properties as optimized crystal structures, band structures, partial and total densities of states, reflectivity, absorption coefficient, refractive index, energy-loss spectrum and dielectric function is calculated. It was found that the electronic parameters for the three isomers are almost similar and our calculated results are in excellent agreement with experimental values and other previous theoretical calculations. At the same time, both of the valence band and conduction band contain contributions from the states of O p and Ti d, which indicates hybridization between these states. In addition, the absorption peaks correspond to the band-to-band transitions from O p states to Ti d states, while the states of O p and the Ti d play a major role in these optical transitions and the values of e1(0) increase as the band-gap decreases.